Evaluating the Feasibility of Yanbu’ul Qur’an Observatory in Menawan Kudus for Lunar Crescent Observation - Iqbal, Muhammad Maulana; Habib, Muhammad Akmal; Ramdhani, Fajri Zulia (Al-Hilal: Journal of Islamic Astronomy, 2025)
The Yanbu’ul Qur’an Observatory in Menawan Kudus, Indonesia, functions as a site for crescent moon (rukyat al-hilāl) observations and Islamic astronomy education. Despite conducting various observation activities, successful hilāl sighting has only occurred during Zulhijjah 1443 H, primarily due to light pollution, limited horizon clarity, and low contrast between the moon and the horizon. This field study analyzes primary data on observatory infrastructure, horizon conditions, sky brightness, and climatological factors, along with secondary data from observation records (2022–2023). The findings indicate two key points: (1) the observatory significantly supports astronomy education at the Yanbu’ul Qur’an Islamic Boarding School, and (2) it is moderately feasible for hilāl observation based on parameters from the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG), including favorable westward orientation, minimal obstructions, elevated location, low light pollution, and reliable electricity and internet access.